Dividing and uniting Germany - Thomaneck, Jürgen (Making of the contemporary world., 2001)
"Dividing and Uniting Germany is an introduction to the process which led to the division of Germany in 1949, and its unification in 1990. While Germany is now politically united, it is still economically, socially and culturally deeply divided along the east-west axis, and this book also explores these problems facing post-unification Germany." "Dividing and Uniting Germany provides an introduction to the challenges which Germany faced in its recent past and the problems still confronting it today."--Jacket